1978
DOI: 10.1002/ajh.2830050110
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin disease and red cell aplasia

Abstract: A teenage boy with mixed-cellularity Hodgkin disease presented with severe anemia secondary to pure red cell aplasia of marrow without evidence of lymphomatous infiltration or hemolysis. In vitro studies of the patient's serum demonstrated an inhibitor of erythropoietin activity which appeared to be an IgG but which did not directly bind erythropoietin. The patient's anemia resolved and the inhibitor disappeared following chemotherapy for Hodgkin disease. Presumably, the inhibitor was directed at a very early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Hauswirth et al have analyzed more than 100 reported cases in the literatures of non-CLL non-Hodgkin's lymphoma associated with autoimmune hemolytic anemia (AIHA) or Evans' syndrome, and they have reported that warm antibody mediated AIHA was more frequent in B-cell lymphomas, while cold antibody mediated AIHA predominantly occurred in T-cell lymphomas [34]. Some reports demonstrated that serum immunoglobulin showed an inhibitory activity against erythropoiesis in vitro [7,9,21]. Theoretically, the pathogenesis of PRCA in lymphoma patients can PROVECIP, procarbazine, vinblastine and cyclophosphamide, prednisone; R-FND, rituximab, fludarabine, mitoxantrone and dexamethasone; immunoab, immunoabsorbance; CsA, cyclosporine A; EPO, erythropoietin; IVIG, intravenous immunoglobulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hauswirth et al have analyzed more than 100 reported cases in the literatures of non-CLL non-Hodgkin's lymphoma associated with autoimmune hemolytic anemia (AIHA) or Evans' syndrome, and they have reported that warm antibody mediated AIHA was more frequent in B-cell lymphomas, while cold antibody mediated AIHA predominantly occurred in T-cell lymphomas [34]. Some reports demonstrated that serum immunoglobulin showed an inhibitory activity against erythropoiesis in vitro [7,9,21]. Theoretically, the pathogenesis of PRCA in lymphoma patients can PROVECIP, procarbazine, vinblastine and cyclophosphamide, prednisone; R-FND, rituximab, fludarabine, mitoxantrone and dexamethasone; immunoab, immunoabsorbance; CsA, cyclosporine A; EPO, erythropoietin; IVIG, intravenous immunoglobulin.…”
Section: Discussionmentioning
confidence: 99%
“…We found twenty-two reported cases of lymphoma-associated with PRCA and these can be classified into two groups based on the chronological sequence in the onset of lymphoma and anemia. Twelve patients presented with lymphoma and PRCA simultaneously (Table IV) [7][8][9][10][11][12][13][14][15][16][17][18], 10 patients developed PRCA following lymphoma (Table V) [5,[19][20][21][22][23][24][25][26][27]. Histologic subtypes of lymphoma varied.…”
Section: Literature Searchmentioning
confidence: 99%
“…The balance has swung in favour of a derivation from the mononuclear phagocyte system, though this is by no means universally accepted. [200][201][202] Suspect biopsies were characterised by small granulomatous foci in the endosteal regions, consisting of lymphocytes, plasma cells, histiocytes and mast cells within a network of reticular fibres and capillaries. The incidence of these sarcoid-like granulomatous foci was 2%.…”
Section: Lymphoproliferative Disordersmentioning
confidence: 99%
“…IgG Fc-receptorpositive T cells were found to be markedly increased in CLL-PRCA and different studies indicated that these cells induce the erythroid progenitor growth im pairment [17,5,[7][8][9]18]. However, a similar inhibi tion was not induced by the same phenotypic T cells from normal individuals [4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%